Dermoscopic features of distal lateral subungual onychomycosis - Thansiha Nargis; Malcolm Pinto; Manjunath Mala Shenoy; Spandana Hegde (Wolters Kluwer Medknow Publications, 2018)
Background: Onychomycosis is a very common disease and accounts for upto 50% of the diseases affecting the nail apparatus. Diagnosis of onychomycosis is usually confirmed with the help of a potassium hydroxide (KOH) mount and fungal culture. Onychoscopy can be a handy and additional tool for the diagnosis. Aims and Objectives: To determine the dermoscopic findings in distal lateral subungual onychomycosis (DLSO). Materials and Methods: A prospective study of 60 nails with a clinical and mycological diagnosis (KOH with Chicago sky blue positive) of DLSO. Dermoscopic examination was performed using a Heine delta 20 plus dermatoscope and the features were recorded. Results: Longitudinal striae and jagged proximal edges seen in all 60 (100%) patients. Intermittent spiked pattern was seen in 47 nails (78.3%). Chromonychia and distal irregular termination were noticed in 23 (38.3%) and 7 (11.7%) nails, respectively. Conclusions: Onychoscopy can be used as an important diagnostic tool while evaluating nail disease, especially in DLSO. Limitations: Small study sample and lack of comparison with other nail diseases that manifests with distal onycholysis.